The effect of work fulfilment on job characteristics and employee retention: Gen Y employees - Koon, Vui Yee*; Khoo, Paggy * (Sage, 2018)
Job characteristics are considered a contributing factor for the retention of employees at work, but the mechanism behind this relationship remains unclear. The current study aimed to analyse work fulfilment as mediators and age among Generation Y (Gen Y) as moderators of the relationship between task and knowledge characteristics and employee retention based on self-determination theory (SDT). Data were collected from 153 Gen Y employees in Klang Valley, Malaysia and analysed using partial least squares (PLS). The results supported the predicted mediating role of work fulfilment with gender and educational level as control variables. Various ages among Gen Y have no differences within the studied relationships. Implications, limitations of these findings and directions for future research are further discussed to improve the retention of employees in the workplace.